Repairing sciatic nerve injury with self-assembling peptide nanofiber scaffold-containing chitosan conduit - Shen, Xuezhen; Qu, Feng; Pei, Yilun; Lei, Simeng; Xia, Suhang; Liang, Jing; Li, Shan; Sun, Xun; Liu, Liang (Frontiers in Neurology, 2022)
Background: An increasing number of nerve guide scaffolds have been used to replace the ‘gold-standard’ autologous nerve graft for repairing peripheral nerve defects, but nerve regeneration is usually far from complete. Methods: Here, we designed and prepared two functionalized self-assembling peptide (SAP) with IKVAV and KLT sequence, which were derived from the combination of laminin and VEGF, respectively. Their mixtures were also obtained to combine the effects of neuroprotective and neurotrophic and proangiogenic factors. Results: The beneficial effect of peptide gels on nerve regeneration was evaluated in vitro using Schwann cells (SCs). As a useful intraluminal filling, a three-dimensional (3D) functionalized Self-assembling peptide (SAP) nanofiber hydrogel was formed in the hollow lumen of chitosan conduits under physiological conditions. In vivo, the combination of the two functionalized SAP gels containing a chitosan nerve conduit significantly accelerated nerve healing and enhanced morphological repair. Conclusion: Based on the current findings, the combined application of two functionalized SAP gels with chitosan nerve conduit is a promising therapy for the engineering of peripheral nerve regeneration.